Chromatographic Methodologies for Analysis of Cocaine and Its Metabolites in Biological Matrices - Valente, Maria João; Carvalho, Félix; Bastos, Maria de Lourdes; Carvalho, Márcia; Pinho, Paula Guedes de (IntechOpen, 2012)
None